The impact of nutritional status on the process of formation of pressure ulcers in a patient in intensive care after injury cerebro-cranial - Pierzak, Monika (Journal of Education, Health and Sport, 2018)
Introduction: Pressure ulcers are chronic wounds of very serious social and economic problem. With advances in medicine and the extension of human life, every day they involve ever growing group of patients. Despite much progress in medicine and the progress in the techniques of cultivating chronic wounds, pressure sores are a problem, which for many years is a blemish on for many doctors and nurses. Material and Methods: A 46 year old male, professional driver status. From the interview with the family that the patient smoked about 15 cigarettes a day, no alcohol, he ate irregularly, fed on due to the nature of the work. Height 183 cm, weight 87 kg at the hospitalization day. Patient underwent surgery, the right parietal craniotomy. Intracerebral hematoma has been removed, breaking raised removed invaginated compromise bone. At the time of adoption in the branch, he was unconscious, intubated connected to a ventilator to breath surrogate mode IPPV, under the influence of anesthetics. Sedation infusion of 2% Propofol, Nalpain.Aim: The impact of the nutritional status of a patient with craniocerebral trauma wounds to the formation of bedsore.Results: Taking into account the results of the questionnaire NRS-2002, the scale Norton, Braden, interview, physical examination, symptoms, anthropometric measurements, biochemical and immunological in the initial period and 30 days of hospitalization can be estimated that the nutritional status of the patient is abnormal, which significantly influences the risk bedsore wounds uprising. Conclusions: The risk of complications such as chronic wounds-pressure ulcers in the patient have beenvery large. This is related to the general state of the patient's diabetes type II, with baseline nutritional status, infections, hypercatabolism resulting from craniocerebral trauma. Back to the patient's health requires large amounts of protein and energy. The patient's condition at the time of adoption in the branch was very heavy, unconscious patient, the surrogate breath, undernourished.Key words: chronic wound, bedsore, nutritional status, prevention